A educação moral e cívica e sua produção didática: 1969-1993 - Filgueiras, Juliana Miranda (2006)
This research aims to present the constitution of the school subject Moral and Civic Education which was made obligatory by the Military Regimen in 1969. This subject was created by the Military Regimen ideology and goes through many changes, but remains obligatory in school curriculums until 1993. By creating the MCE, the Military Regimen intended to make it responsible for the political formation of the Brazilian citizen. By doing it, this responsibility was taken away from other subjects like history and geography. The knowledge related to patriotism was transferred from these subjects and presented as special topics of Moral and Civic Education. The subject should educate the citizen to fight subversive ideas communism, and create a religious moral. Several textbooks were produced for the subject, which are considered privileged study sources, because they expose the proposals presented by the oficial curricular programs. Another important aspect was the creation of an specific entity to rule the subject the National Comitee for Moral and Civism, responsible for the implementation and maintenance of the doctrine of the subject and also responsible for the evaluation and approval of the textbooks. This entity fought for space with the Federal Council of Education through all the studied period. A continuous shock was noticed between the two entities, especially in relation to the teaching lines of direction of MCE